2014
DOI: 10.1248/bpb.b14-00362
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity Induced by Piperacillin–Tazobactam in Late Elderly Japanese Patients with Nursing and Healthcare Associated Pneumonia

Abstract: This study aimed to clarify the efficacy, safety, and pharmacokinetics of piperacillin-tazobactam (PIPC-TAZ) in late elderly Japanese patients. This is the first antimicrobial pilot study in late elderly patients with nursing and healthcare associated pneumonia. After PIPC-TAZ administration, PIPC concentrations in plasma were measured chromatographically and the pharmacokinetic parameters were estimated. Efficacy, safety, and bacteriological evaluations were also carried out. The mean age was 85.0 years old a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…It would be ideal to calculate the appropriate dose of TZP to achieve the maximized probability of target attainment using stimulation techniques, which could provide individualized dosing regimens and enable an accurate inter-race comparison. In addition, previously reported toxicity of piperacillin associated with impaired renal function should be compared between ethnic groups, because categorizing dosing by the degree of crude renal function may to be too high or low for patients in the same category, according to race [ 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be ideal to calculate the appropriate dose of TZP to achieve the maximized probability of target attainment using stimulation techniques, which could provide individualized dosing regimens and enable an accurate inter-race comparison. In addition, previously reported toxicity of piperacillin associated with impaired renal function should be compared between ethnic groups, because categorizing dosing by the degree of crude renal function may to be too high or low for patients in the same category, according to race [ 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, using Table 5 prepared by this study, we were able to present the optimal dosing regimen for the elderly in the late stage that takes into account not only CL cr but also the MIC. Additionally, we have already reported that renal dysfunction, especially CL cr of less than 40 mL/min, could be an influential factor for nephrotoxicity induced by PIPC/TAZ-induced nephrotoxicity in late elderly patients [34]. Therefore, although the recommended dosing regimens are shown in Table 5, from the viewpoint of safety, the administration of PIPC/TAZ should be performed more carefully in patients with CL cr values of 30 mL/min or less.…”
Section: Discussionmentioning
confidence: 99%
“…32) However, the following exclusion criteria were applied: patients younger than 18 years old, patients without records of height or weight essential for calculating the BMI, patients with BMI < 30 kg/m 2 , patients without information regarding diagnosis and TZP administration (e.g., indication, dosage, and duration of treatment), patients without lab value information, patients who underwent TZP treatment for less than 72 hours, patients who received TZP again due to the same affliction in the same year, or patients allergic to penicillins, cephalosporins, or beta-lactamase inhibitors. 3,10,25,29,32)…”
Section: Study Populationmentioning
confidence: 99%
“…According to a study by Karino et al in Japan, cautious TZP administration and monitoring was necessary in elderly patients with kidney dysfunction, particularly those with CrCl less than 40 mL/min owing to serious nephrotoxicity (although TZP is effective against hospital-acquired pneumonia). 10) Functional renal mass can be measured through the glomerular filtration rate (GFR) calculated from inulin injections, but this method is clinically impractical due to the time required for IV infusion and urine collection; hence, the Cockcroft-Gault (CG) equation is typically utilized to measure renal function. 11) The pharmaceutical industry also uses the CG equation to determine renal dosage adjustments for different drugs.…”
mentioning
confidence: 99%